The relationship between social support and depression among older adults with hypertension in urban communities: mediating effects of coping styles - Li, Dan; Jie, Jin-Hua; Li, Hong; Xia, Xue-Mei; Zhang, Yilin; Yang, Yan; Xiang, Jianjun; Zhuang, Hai-Lin (Frontiers in Psychiatry, 2025)
BackgroundOlder adults with hypertension are at an increased risk of depression. Social support and coping style significantly influence this risk, with social cognitive theory suggesting that social support can affect an individual’s coping style, and coping style can affect the effective use of social support. However, the mediating role of coping style in the relationship between social support and depression in older hypertensive patients remains unclear. This study aimed to explore the inter-relationships between social support, coping style and depression in older hypertensive patients within a community setting, and to investigate the mediating effects of coping style.MethodsA cross-sectional questionnaire survey was conducted with 4211 older hypertensive patients from Fuzhou, Fujian Province, China. Participants were assessed for depression, social support, coping styles, and general demographic information. Pearson correlation analysis was employed to test the correlation between variables. Mediation effect test was conducted using SPSS macro program PROCESS with Bootstrap based Model 4, after controlling for confounding factors.ResultsA total of 4211 valid questionnaires were collected, yielding an effective response rate of 98.6%. The average depression score among participants was 7.99 ± 4.92 points, with 29.5% of respondents experiencing varying degrees of depression. Both social support and coping style were associated with depression in older hypertensive patients. Specifically, objective support, subjective support, support utilization, and positive coping style were negatively correlated with depression, with correlation coefficients of -0.159, -0.160, -0.145, and -0.163, respectively. Conversely, negative coping style was positively correlated with depression, with a correlation coefficient of 0.170. Mediating effect analysis showed that coping style played a mediating role between social support and depression. Social support negatively moderated depression through positive coping style (moderating effect =-0.020, Bootstrap 95%CI [-0.027, -0.138], mediating effect value was 15.87%), while it positively influenced depression through negative coping style (moderating effect =0.012, Bootstrap 95%CI [0.008,0.017], intermediate effect value =9.52%).ConclusionSocial support exerts a direct negative effect on depression, while coping styles mediate the relationship between social support and depression. Interventions to reduce depression in this population should focus on enhancing social support (across objective, subjective, and utilization aspects) and promoting positive coping strategies, thus strengthening psychological resilience and improving overall health and quality of life for older adults with hypertension.